The Effects of Flipped Learning on Student Achievement and Interest Across Different Learning Styles in Polytechnic Education - Madar, Ahmad Rizal; Hamid, Hashima; A.Jalil, Noor Azyani; Setiyani; Amiruddin, Mohd Hasril; Abdullah, Nurhanim Saadah (Journal of Technical Education and Training, 2025)
Flipped learning is designed to encourage students to be more active and be able to give more accurate answers. In addition, students will face fewer problems with their learning if they control their learning patterns. Hence, this study aims to identify the difference in the level of score achievement and interest of polytechnic students based on their learning styles. This research instrument consists of a questionnaire about interests and Index Learning Styles (ILS), ii) an e-learning guidebook, and iii) pre-test and post-test questions. MANCOVA analysis was used to answer the question to determine whether there was an increase in the level of student achievement and interest. The results of the MANCOVA analysis for the four breakdowns of student categories, PA-IV, PA-IA, PR-IV, and PR-IA, show no significant difference for the treatment and control groups. The use of the flipped learning method for the treatment group did not show an optimal effect, especially for their academic achievement and interest. This is because using the flipped learning method only takes eight (8) weeks. After looking into more details, if this method's flipped learning application for an extended period, the possibility of changes in academic achievement and student interest can be seen more significantly. However, to some extent, using this flipped learning method in the teaching and learning activity can improve academic achievement and student interest to be more outstanding and positive, especially for Electrical Technology courses.